Hemorrhoidal Disease in Sedentary Adults and Homeopathic Approach (Homoeopathy for All, 2025)
In today’s digital era, prolonged  sitting, minimal physical activity,  and poor dietary habits have  become a part of everyday life.  The increasing dependence on  computers, smartphones, and desk based occupations has given rise  to a sedentary lifestyle; one that  predisposes individuals to a variety  of health conditions, including piles  or hemorrhoids. Long working  hours, irregular eating patterns,  stress, and digital fatigue have made  this condition increasingly common  among modern professionals.
Keywords: hemorrhoidal cushions; chronic constipation; severity of hemorrhoids; photocoagulation